391 Prophylactic Antibiotics and Sepsis in Neonates Born through Meconium Stained Amniotic Fluid (MSAF) - a Randomized Controlled Trial. (October 2012) - Goel, A; Nangia, S; Saili, A; Sharma, S; Randhawa, V
Abstract : Background: Most newborns with MSAF receive antibiotics as meconium has been incriminated to increase incidence of both intraamniotic and postnatal sepsis. Due to rising concerns about inadvertent overuse of antibiotics, this practice needs to be systematically evaluated. Objective: To evaluate the role of prophylactic antibiotics on occurrence of neonatal sepsis in term neonates born through MSAF. Methods: Out of 359 eligible neonates, 109 were excluded based on exclusion criteria and remaining 250 randomized to Study (Antibiotic group - receiving first line antibiotics for 3 days), and Control (No Antibiotic) group. Both the groups were evaluated for sepsis on clinical and laboratory parameters. All neonates were monitored for complications related to MSAF. After discharge babies were followed up for sepsis till 28 days of life. Results: 121 babies were randomized to Antibiotic group and 129 to No Antibiotic group. Of the total 250 neonates, 24 (9.6%) developed suspected sepsis, 8 in Antibiotic (6.6%) and 16 in No Antibiotic group (12.4%) (p= 0.12, OR 0.5, 95% CI: 0.21–1.22). Culture proven sepsis occurred in 12 babies (4.8%), 5 in Antibiotic and 7 in No Antibiotic group (4.13% vs. 5.42%, p= 0.63, OR 0.75, 95% CI: 0.23–2.43).The incidence of mortality (2.5% vs. 2.3%), meconium aspiration syndrome (18.2% vs. 15.5%, p=0.57) and other complications like air leaks, PPHN and intracranial hemorrhage was comparable between the two groups. Conclusions: Prophylactic antibiotics in neonates born through MSAF do not reduce the incidence of sepsis. Hence, empiric use of antibiotics without documented evidence of infection should be avoided.